EXPLORING STUDENTS’ PERCEPTIONS ON NATIVE ENGLISH SPEAKER TEACHER (NEST) TEACHING STYLES - Budiman Budiman; Maryati Salmiah (Tell-us Journal)
This study investigates English as a Foreign Language (EFL) students’ perceptions of the teaching styles of native English speaking teacher (NESTs). Using a qualitative phenomenological method, the study investigated students' experiences, preferences, and concerns while learning from native English-speaking lecturer. Data were gathered through questionnaires and semi-structured interviews with 28 fifth-year English language students at a university in North Sumatra, Indonesia. The findings demonstrate that, in general, students have various positive perceptions regarding native speaker teacher, particularly their participatory teaching techniques, structured assignments, effective classroom management, and strong communication abilities. Furthermore, students enjoy the affective qualities of teaching, such as passion, empathy, and drive, which help to create a positive learning environment. However, some students had difficulties due to cultural differences and a linguistic barrier. This study highlights the significance of communicative and learner-centered learning strategies in foreign language acquisition.  The findings suggest that pairing NEST teacher with non-native English teachers can result in a more balanced and effective language learning experience.  Although this study produced useful insights, its scope was confined to a single college, indicating the need for a larger study that covers other universities and varied language learning contexts.  Future research should look at the long-term impacts of NNEST training and ways for bridging cultural and language gaps in the English classroom.